KEZUHUDAN ISA AL-MASIH DALAM KITAB AL-ZUHD WAâL-RAQÄâIQ DAN AL-ZUHD - Muhammad, Hasyim (IAIN Walisongo Semarang, 2012)
Abstract Â The ascetisc of Isa al-Masih is the most polular model in strengtening the ascetism doctrines among tasawwuf experts in clasical periods. At least it was depicted in clasical sunnite sufism that narrated the messages and stories about the escatism of Isa al-Masih. Above all, the more valid source, i.e. al-Qurâan and al-hadits are more than enough to strengten the doctrine of ascetism for the tasawwuf experts (sufi). Ascetism of Isa al-Masih was conformable to the concept of ascetismof the sufi, which meant that have nothing and belong to nothing (lÄ yamliku shaian walÄ yamlikuhu shaiun). Ascetism is not only merely spiritual position which is depicted in tasawuf, but ascetisme in this context is the spiritual it self. Â *** Asketisme Isa al-Masih merupakan model yang paling populer dalam memperkuat doktrin asketisme di kalangan ahli tasawuf dalam periode klasik. Setidaknya itu digambarkan dalam sufisme sunni klasik yang menarasikan pesan dan kisah mengenai asketisme Isa al-Masih. Di luar itu semua, sumber yang lebih valid, yaitu al-Qurâan dan hadits lebih dari cukup untuk memperkuat doktrin asketisme bag para ahli tasawuf (sufi). Asketisme Isa al-Masih sesuai dengan konsep asketisme sufi yang artinya tidak memiliki apa-apa dan bukan milik siapa-siapa (lÄ yamliku shaian walÄ yamliku shaiun). Asketisme bukan sekedar posisi spiritual yang digambarkan di dalam tasawuf, tetapi asketisme dalam konteks ini adalah spiritual itu sendiri. Â Keywords: asketisme, Isa al-Masih, doktrin, sufi, spiritual